2018
DOI: 10.7567/jjap.57.03ed01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radical initiators, polymerization inhibitors, and other agents on the sonochemical unzipping of double-walled carbon nanotubes

Abstract: The mechanism of graphene nanoribbon synthesis by the sonication-assisted unzipping of carbon nanotubes (CNTs) was investigated utilizing 4-methoxyphenol and 1,4-dimethoxybenzene as moieties of poly[(m-phenylenevinylene)-co-(2,5-dioctoxy-p-phenylenevinylene)]. The obtained results revealed that unzipping was promoted by 4-methoxyphenol owing to the facile abstraction of its phenolic hydrogen by sonication-generated radicals on CNTs, whereas 1,4-dimethoxybenzene did not facilitate unzipping, since its methoxy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[ 20 ] PmPV is required during the procedure because its phenylenevinylene structure aids in the production of a hydrogen or radical donor species via sonication. [ 22 ] Given the PmPV's molecular size, we predicted that it would predominantly adsorb on the surface (= outside wall) of DWNTs, and so causes defects preferentially on the outer walls of DWNTs (Figure 6a). The current TERS studies on intermediate yGNRs successfully produced complementary evidence of this, with a greater defect density seen on sGNRs from the outer DWNT wall than those from the inner wall (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] PmPV is required during the procedure because its phenylenevinylene structure aids in the production of a hydrogen or radical donor species via sonication. [ 22 ] Given the PmPV's molecular size, we predicted that it would predominantly adsorb on the surface (= outside wall) of DWNTs, and so causes defects preferentially on the outer walls of DWNTs (Figure 6a). The current TERS studies on intermediate yGNRs successfully produced complementary evidence of this, with a greater defect density seen on sGNRs from the outer DWNT wall than those from the inner wall (Figure 6b).…”
Section: Resultsmentioning
confidence: 99%
“…[21] We have recently found that the unzipping of double-walled carbon nanotubes (DWNTs), rather than single-or multi-walled, results in high-yield production of crystalline single-layered GNRs (sGNRs) with a relatively short sonication time (e.g., 20 h for SWNTs and 5 h for DWNTs), in which poly(m-phenylenevinylene-co-2,5-dioctoxy-pphenylenevinylene) (PmPV) acts as both an efficient dispersing agent and radical sources. [20,22,23] Regarding the mechanism of DWNT unzipping, it is observed from atomic force microscopy (AFM) that double-layered GNRs (dGNRs) are first generated, with subsequent sonication leading to the separation of the two graphene layers to form sGNRs. Complementary evidence of this can be found from the presence of partially branched intermediate state GNRs (i.e., y-shaped GNRs) at an early reaction stage (sonication time ≈1 h).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several approaches to obtain sGNRs, [10][11][12] longitudinal unzipping of carbon nanotubes (CNTs) is one of the most common techniques to obtain sGNRs measuring a few nanometers in width. 13,14) In our previous work, we successfully obtained single-layer sGNRs by the unzipping of single-walled [15][16][17] and double-walled [18][19][20] CNTs (SWNTs and DWNTs) and subsequently carrying out sonication. Although sub-10 nm width sGNRs can be produced by unzipping and are suitable for mass production, 13) applying unzipping to the fabrication process of electronic devices remains limited.…”
mentioning
confidence: 99%